Evidenzbasierte perioperative Medizin = Evidence-based perioperative medicine - Probst, Pascal; Klotz, Rosa; Hüttner, Felix; Harnoß, Julian-Camill; Diener, Markus K. (Der Chirurg, 2019)
Perioperative medical interventions are an integral part of modern surgical management. In addition to the main manual aspects of surgical interventions, surgeons must also be familiar with preoperative and postoperative medical interventions. This ranges from the indications for perioperative anticoagulation, handling of drainage, adjusting the perioperative analgesia, prescribing an antibiotic prophylaxis to deciding whether a preoperative bowel preparation is necessary. Therefore, this article exemplifies some areas in perioperative medicine. Based on the best available evidence, it should always be critically assessed whether these perioperative interventions really contribute to the success of the treatment.
Gesehen am 09.10.2019